Inisiasi Klub Literasi Bahasa di SMP Negeri 2 Sukowono Jember - Meiga Rahmanita; Ismailia, Titik; Mariyati, Nanik; Novawan, Adriadi; Mujib, Ihwan Huda Al (BADAN PENERBIT STIEPARI PRESS, 2024)
Literacy is one of the indicators of the nation development. Unfortunately, our people’s literacy is still low and needs to be introduced early to the children. SMP Negeri 2 Sukowono, Jember, also faced the same problem. Their students’ literacy and reading interest were still lacking. Besides, there was not any activtity which accomodate students’ interest in literacy. The community service team proposed a solution to make a Language Literacy Club for this problem. The program was conducted through four steps; preliminary study, planning, implementing, and evaluation. After being implemented to the students, it gained positive responses from both students and teachers. The students enjoyed the activity done in the group so much. Moreover, students’ language ability and confidence increased. Therefore, it can be concluded that the existence of Language Literacy Club is beneficial for the students. Next, an active promotion is needed to attract more students to join this club.